The Effect of Additional Crystalline Materials on Concrete on Sulfic Acid - Sudrajat Budi Utomo; Agung Sumarno (LPPM NAROTAMA UNIVERSITY, Indonesia, 2021)
An acidic environment can be found in many situations such as acid rain, fog, acidic ground water, sewage systems and chemical plants. Acidic environments containing acidic chemicals can slowly damage concrete from the edges and corners of the concrete by releasing it granules of concrete particles so that the concrete becomes porous. The use of crystaline material or crystal material that can be used as added material in concrete to improve the watertightness and resistance of concrete to acid because it is able to fill and clog pores, capillaries, micro crevices , and other holes with crystalline form that are not soluble and are very resistant to formation, research was conducted to determine the effect of crystalline material on normal concrete using type I and type V cement against, density, concrete compressive strength and workability. Tests carried out by the use of crystalline material mix PRAH CA-1000 and mix PRAH CA-5000 with a variation of 0.5% - 1.2%. The test object used is Cylinder 10 cm x 20 cm by 60 pieces, testing is carried out at the age of concrete 3 , 7, 28 days for concrete density and 28 days for compressive strength. The results of the study note that the results of the addition of Crystalline and the use of different types of cement in normal concrete can affect the compressive strength of concrete and do not affect the traceability, optimal type of Crystalline Admixture in testing concrete specimens after exposure to sulfuric acid (H2SO4) is mix PRAH CA-5000.